Smart Crop Adaptability and Monitoring (SCAM) - BIN MOHD SAKRI, MUHAMMAD HAZIM (Progress in Engineering Application and Technology, 2023)
IoT is quite important in the agricultural sector. This study mostly applies to the topic of agriculture. The study discusses smart irrigation and farming systems based on IoT. The ultimate goal of this article is to create a model that can automatically irrigate, chill, and light artificially grown plants. We can grow the plant appropriately if we are aware of the values of different characteristics, such as light intensity, humidity, moisture, and temperature. Three sensors make up the system, which measures the humidity, wetness, and temperature of plants. The hardware for the plant is all automatically turned on by the board if any of the values deviate from the standard. The NodeMCU ESP32 board, lamp, voltage regulator, and relay that manages the motor and cooling fan are used to accomplish this. The user is informed about the crop or plant status via Blynk application. The several sensors feed data to the NodeMCU ESP32 board, which has been programmed with if-else conditions and Blynk control. The relay then passes the orders on to turn on or off the hardware depending on the conditions. The main benefit of this paper is that it reduces the amount of physical labor required, provides adequate lighting, maintains temperature and humidity levels, and automates watering with the aid of devices, allowing for the growth of healthy plants. Even elderly individuals may operate a farm with ease. The pepper plant was successfully grown on the paper using an automated procedure and monitoring. We were able to have a healthy farming operation because to this practice and the Internet of Things. Increasing agriculture also aids in improving the nation's economic situation.